2010
DOI: 10.1186/1471-2229-10-210
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of polycyclic aromatic hydrocarbons in subcellular root tissues of ryegrass (Lolium multiflorumLam.)

Abstract: BackgroundBecause of the increasing quantity and high toxicity to humans of polycyclic aromatic hydrocarbons (PAHs) in the environment, several bioremediation mechanisms and protocols have been investigated to restore PAH-contaminated sites. The transport of organic contaminants among plant cells via tissues and their partition in roots, stalks, and leaves resulting from transpiration and lipid content have been extensively investigated. However, information about PAH distributions in intracellular tissues is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(82 citation statements)
references
References 31 publications
1
80
0
1
Order By: Relevance
“…The subcellular distribution of organic contaminants has important effects on their accumulation, translocation, and metabolism in different plant species and cultivars (Gao et al, 2011(Gao et al, , 2013Kang et al, 2010). The first barrier that protects the protoplast against contaminant toxicity, plant cell walls, can bind organic contaminants due to cell wall components such as pectin, cellulose, hemicellulose, and lignin, restricting transport of the contaminants across cell membranes (Kang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The subcellular distribution of organic contaminants has important effects on their accumulation, translocation, and metabolism in different plant species and cultivars (Gao et al, 2011(Gao et al, , 2013Kang et al, 2010). The first barrier that protects the protoplast against contaminant toxicity, plant cell walls, can bind organic contaminants due to cell wall components such as pectin, cellulose, hemicellulose, and lignin, restricting transport of the contaminants across cell membranes (Kang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in phytodegradation studies have come to light in the application of rye grass (Lolium multiflorum) and bermudagrass (Cynodon dactylon) in degrading alkylated two ring naphthalenes (White, Wolf, Thoma, & Reynolds, 2006). In their contribution on distribution of PAHs in sub-cellular root tissue, Kang, Chen, Gao, and Zhang (2010) and Ward, Singh, and Van Hamme (2003) had revealed that using L. multiflorium, pyrene was most adsorped in the root of the plant than other PAHs. Previous studies from Simonich andHites (1994), Bakker, Vorenhou, Sum, andKollôffel (1999) and Gao and Zhu (2004) are of the opinion that the efficiency of plant uptake and metabolism of PAHs depended on the morphology of the plant system.…”
Section: Phytodegradationmentioning
confidence: 99%
“…PAHs have a relatively low solubility in water and low Henry's law constants, but are highly lipophilic and have high octanol-water partition coefficients (K ow ), while the phospholipid bilayer of the cell membrane is externally hydrophilic and internally lipophilic. The unique characteristics of the phospholipid bilayer cause internal aggregation of PAHs inside the membrane structure (Kang et al, 2010;Haritash and Kaushik, 2009). The phospholipid layer can create a hydrophobic region for accumulation of hydrophobic compounds within the cell membrane.…”
Section: Study On the Localization Of Phe In P Vittatamentioning
confidence: 99%
“…Studies have demonstrated that hexane, paraffins, and PAHs enter the membrane via vesicles (Sikkema et al, 1994;White et al, 1981). Kang et al (2010) investigated the subcellular distribution of pyrene and PHE in the perennial, ryegrass (Lolium perenne L.), and found that the compounds first adsorb to the cell wall of the roots, then enter the organelles within the cell via the cell membrane. Ren et al (2010) compared the transmembrane transport of four typical lipophilic organic compounds, and proposed that PAHs in the extracellular medium enter the cytoplasm in a steady flow through the partition-inverse releasebinding mechanism.…”
Section: Study On the Localization Of Phe In P Vittatamentioning
confidence: 99%